The Strategy to Increase Public Interest in Managing Building Permits in Mentawai Islands Regency - Sahad Pardamaian; Khairul Khairul; Hurip Pratomo (Pascasarjana, Universitas Negeri Padang, 2022)
This study aims to explain the strategy of the Mentawai Islands Regency One Stop Investment and Integrated Services Service to increase public awareness in dealing with Building Permits (IMB). This research is qualitative by conducting interviews with informants totaling 19 people from local government agencies and 15 people from the community to find out the PEMDA's strategy in increasing public awareness of managing IMB. The results of the study show that the community thinks they are building in their yard, why do they have to take care of a permit, then the building has no impact on the surrounding environment. Knowledge of building permits was obtained from the government, which had placed banners and billboards along the corridors. However, they do not want to take care of the IMB because it is not urgent and legalized and there are no applicable sanctions. The strategy to increase public awareness in managing the IMB is to conduct a lot of outreach and to place service assistant offices in the sub-districts. The next strategy is to improve the quality of IMB granting services by periodically training officers.